Stress concentration in composite laminates - Leong, Hon Yin (Nanyang Technological University, 2021)
This report aims to carry out the stress analysis of orthotropic unidirectional lamina with one circular hole and then two circular holes under static remote and uniform tensile load using the Boundary Element Method. Three different materials are being used in the modelling, namely Boron Epoxy, Kevlar-49 Epoxy and HMS Carbon Epoxy. The results for the normalized stress distribution and normalized failure function for a range of fiber orientations in each of these materials and geometric parameters are presented. The parametric variations include the size of the hole, the distance between two holes and the fiber orientation of the lamina. It was found that in composites, the locations of failure may not necessarily coincide with the locations of highest stress concentrations for the cases as in isotropic materials.